Peran Mahasiswa Kuliah Kerja Nyata (KKN) dalam Gerakan Konservasi Lingkungan dan Penerapannya di Kecamatan Pondokgede - Mishelei Loen; Imam Wibowo; Harry Indra; Ismail Razak; Nuridin Nuridin; Munawaroh Munawaroh; Rosdiana Rosdiana; Dhistianti Mei Rahmawantari; Diajeng Reztrianti; M. Kausar Maulana; Yuaniko Paramitra; Tatag Herbayu; Arry Dwi Syahputra; Nino Nopriandi Saleh; Arief Rachmawan Assegaf; Arief Syaf Safrianto; Iwan kurniawan Subagja; Muhammad Harri (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
The Community Service Program (KKN) of the Faculty of Economics, UNKRIS, aims to raise awareness and change behavior among the community in Pondokgede sub-district regarding the environment, starting with the household environment in handling organic and inorganic waste through composting and the use of Biopori Infiltration Pits (LRB), waste banks, and greening for Green Open Spaces (RTH). The method used in this study is qualitative analysis. Before the KKN FE UNKRIS activities were implemented, several steps were taken to ensure the smoothness and effectiveness of the program, including preparation, implementation, and evaluation. Overall, the KKN FE UNKRIS program in the environmental conservation movement and its implementation in Pondokgede sub-district has had a positive impact on accelerating the development of Pondokgede sub-district, as evidenced by the improvement in community behavior toward the environment and the level of community satisfaction with the KKN FE UNKRIS program. The implications of this KKN program include the need for continuous monitoring to ensure that community awareness of a clean and healthy environment continues to increase. Additionally, the program should be continued until the stage of utilizing the results of waste processing generated by each community in Pondokgede.